Pengaruh Model Pembelajaran Jarak Jauh Berbasis Google Classroom - Putri, Gesa Kharisma; Setyo Dewi, Yuli Ani (Pendidikan Agama Islam, 2019)
The government has set up distance education based on Law No. 20 Year 2003 About Educational system (SISDIKNAS), which were referred to the distance education is education that the students are apart from educators and learning to use various sources of learning through technology, general problems education in Indonesia, the learning system is not good, seen from the learning methods, instructional media, and materials that are still not appropriate in their use. It is causing the low results of learning of students, which is influenced by the various methods of learning are less precise. The method used in this study is an experimental method. The form of this research is in the form of pre-test and post-test of the experimental group and the control group to determine student learning outcomes. From the average value of the pre-test of the control class and experiment, with the post-test value of the control class and experiment. Rated Average grade control in the pre-test is worth 75.16 and the post-test worth 70.28. there is a decrease in the average value of the conversation class by 4.88. While the value of the average class experiment in pre-test is worth 77.13 and the post-test worth 88.00. thus, an increase in the value of the average grade of experiments at 10.87. it means that there is an increase in the value of the average after the learning using Google Classroom, although not too significant.